DRAWING CONTAGION: AN ANALYSIS OF COVID-19 COMICS - S., Saran; James, Meera Elizabeth; P., Jyothimol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
When the world was suddenly caught up in the quagmires of Covid-19 pandemic, many attempts at providing awareness happened at personal, local and global levels. The outbreak of the pandemic witnessed an outbreak of narratives to shape a collective understanding about the disease. Along with the verbal narratives visual culture also contributed to the shaping of the culture of contagion. Comics have long been part of the visual culture of medicine. Graphic medicine is a novel field of medical humanities which is an intersection of the discourse of medicine and comics. This paper analyses how comics are used as a cultural artefact to sensitise the public during the Covid-19 pandemic period. It also attempts at analysing how the spatio-temporal tropes of the comics have made visible the invisible virus that spread havoc across the globe. The paper analyses the Covid comics that emerged during the period and how it has influenced the global public in shaping its culture of contagion.